Nasal Microbiome Change During and After Exacerbation in Asthmatic Children - Liu, Tsunglin; Lin, Cheng-Han; Chen, Yi-Lin; Jeng, Shuen-Lin; Tsai, Hui-Ju; Ho, Chung-Liang; Kuo, Wen-Shuo; Hsieh, Miao-Hsi; Chen, Pei-Chi; Wu, Lawrence Shih-Hsin; Wang, Jiu-Yao (Frontiers in Microbiology, 2022)
Airway and gut microbiota are important in asthma pathogenesis. Although several studies have revealed distinct microbiota in asthmatic airways at baseline compared to healthy controls, limited studies compared microbiota during acute exacerbation (AE) and in the recovery phase (RP) in the same asthmatic children. We aim to investigate association between microbiota and asthma status in children and explore their relationship with clinical features of asthma. We recruited 56 asthmatic children and investigated their nasal, throat, and stool microbiota during AE and in the RP. Totally, 320 samples were subjected to 16S rRNA sequencing. Although the microbial communities were clearly separated by body site, within each site the overall communities during AE and in the RP could not be distinguished. Most nasal microbiota were dominated by only one or two of six bacterial genera. The domination was associated with mite allergy and patient age only during AE but not in the RP. When moving into RP, the relative abundance of Staphylococcus increased while that of Moraxella decreased. Throat and stool microbiota were not associated with most of the clinical features. Interestingly, stool microbiota during AE was associated with ABO blood type and stool microbiota in the RP was associated with frequency of the subsequent exacerbations. In summary, the association between nasal microbiota and mite allergy only during AE suggests an altered local immunity and its interplay with nasal microbes. Our work provides a basis for studying microbes, and prevention or therapeutic strategy in in childhood asthma, especially during AE.